2014
DOI: 10.1002/2013ja019437
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of sporadic E layer retrieved from COSMIC GPS radio occultation measurements: Wind shear theory examination

Abstract: On the basis of the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC)-measured fluctuations in the signal-to-noise ratio and excess phase of the GPS signal piercing through ionospheric sporadic E (Es) layers, the general morphologies of these layers are presented for the period from July 2006 to May 2011. It is found that the latitudinal variation in the Es layer occurrence is substantially geomagnetically controlled, most frequent in the summer hemisphere within the geomagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

55
236
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(294 citation statements)
references
References 61 publications
55
236
3
Order By: Relevance
“…Specifically, they provided direct proof of the control exerted by the Earth's geomagnetic field on E s for the first time, and this supported the wind shear theory strongly (Haldoupis, 2011). These statistics are further confirmed by Chu et al (2014) and Yeh et al (2012), based on a large amount of COSMIC data. Through both simulation and real-data analysis, Zeng and Sokolovskiy (2010) revealed that the E s cloud aligned with the wave propagation direction could cause defocusing of the GPS RO signal, accompanied by scintillation above and below the defocusing region due to the interference of direct and refracted radio waves.…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…Specifically, they provided direct proof of the control exerted by the Earth's geomagnetic field on E s for the first time, and this supported the wind shear theory strongly (Haldoupis, 2011). These statistics are further confirmed by Chu et al (2014) and Yeh et al (2012), based on a large amount of COSMIC data. Through both simulation and real-data analysis, Zeng and Sokolovskiy (2010) revealed that the E s cloud aligned with the wave propagation direction could cause defocusing of the GPS RO signal, accompanied by scintillation above and below the defocusing region due to the interference of direct and refracted radio waves.…”
Section: Introductionsupporting
confidence: 60%
“…The E s is controlled by the tidal wind and therefore also shows tidal structures in its formation and descent. Main tidal components can be diurnal, semidiurnal, and even terdiurnal and quarterdiurnal (Arras et al, 2009;Chu et al, 2014;Fytterer et al, 2013;Wu et al, 2005). All these factors make the complex E s layer structures understandable.…”
Section: Multiple E S Layers In One Profilementioning
confidence: 99%
See 3 more Smart Citations